The contribution of email volume, email management strategies and propensity to worry in predicting email stress among academics - Jerejian, Ailsa; Reid, Carly; Rees, Clare (Pergamon, 2013)
The present study explored the contribution of email volume, email management and worry in predicting email stress among a sample of Australian academics. The sample comprised 114 academic staff from Curtin University in Perth, Australia. An online survey was conducted to gather data on the target variables. A moderated hierarchical regression indicated that the combined model accounted for a significant 11.90% of the variance in email stress (p = .008, f2 = .135). Worry individually accounted for a significant proportion of the variance (p = .010, f2 = .06, 95% CI [.028, .202]). Email volume also significantly predicted email stress (p = .00, f2 = .057, 95% CI [.011, .079]). Email management did not moderate the email volume and stress relationship. The findings suggest that email stress is impacting upon academic teaching staff and that research on mitigating this stress needs to be undertaken.